2018
DOI: 10.1186/s13018-018-0743-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wiltse’s paraspinal approach and open book laminectomy for thoracolumbar burst fractures with greenstick lamina fractures: a randomized controlled trial

Abstract: BackgroundPosterior short-segment pedicle screw fixation is used to treat thoracolumbar burst fractures. However, no randomized controlled studies have compared the efficacy of the two approaches––the Wiltse’s paraspinal approach and open book laminectomy in the treatment of thoracolumbar burst fractures with greenstick lamina fractures.Materials and methodsPatients with burst fractures of the thoracolumbar spine without neurological deficit were randomized to receive either the Wiltse’s paraspinal approach (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Short-segment Schanz screw fixation implanted in an oblique downward direction can achieve an upward and forward reduction of the anterior column, middle column, and the posterior column, thus resulted in a better reduction of the downward and backward retrodisplaced vertebra. Therefore, with this method, the available reduction of burst fractured vertebra (LSC ≥ 7) and spinal canal decompression can be achieved without laminectomy even if when the spinal stenosis was severe, and therefore, it is better than the screw insertion parallel to the endplates, which hardly reduced the intraspinal bone fragments without laminectomy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Short-segment Schanz screw fixation implanted in an oblique downward direction can achieve an upward and forward reduction of the anterior column, middle column, and the posterior column, thus resulted in a better reduction of the downward and backward retrodisplaced vertebra. Therefore, with this method, the available reduction of burst fractured vertebra (LSC ≥ 7) and spinal canal decompression can be achieved without laminectomy even if when the spinal stenosis was severe, and therefore, it is better than the screw insertion parallel to the endplates, which hardly reduced the intraspinal bone fragments without laminectomy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…When compared to open surgery, MISS has shown equivocal final results but with smaller incision, less intraoperative blood loss, shorter recovery time, less post-operative pain, and higher safety. 10,11 Studies have shown that percutaneous screws have minimal trauma to paraspinal musculature compared to open methods which cause denervation and devascularisation of muscles. 12 The only drawback of MISS over open surgery is a significantly higher amount of radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…By imaging, histology and electrophysiological assessment, Liu et al [11] found that the Wiltse approach for thoracolumbar fractures was accompanied with a lower incidence of multi dus atrophy and denervation, and less fatty in ltration compared with conventional posterior open approach. Pedicle screw xation via Wiltse paraspinal approach has been considered as an effective and minimally invasive approach in treatment of thoracolumbar fracture with neurologic intact for the advantages of simple operation and less trauma [12,13].…”
Section: Discussionmentioning
confidence: 99%